Immune cell C/EBPβ deficiency is associated with hepatic mononuclear defects and spontaneous hepatitis but not steatohepatitis induced liver fibrosis. Issue 11 (27th October 2022) - Moshkovits, Itay; Kaminitz, Ayelet; Reuveni, Debby; Pasmanik‐Chor, Metsada; Brazowski, Eli; Mildner, Alexander; Leutz, Achim; Zigmond, Ehud
Abstract: Background: CCAAT/enhancer‐binding protein β (C/EBPβ) is a transcription factor known to be involved in macrophage differentiation and function, steatohepatitis and liver fibrosis. Methods: Immune restricted C/EBPβ deficient and control mice were investigated in steady‐state and in the CDA‐HFD steatohepatitis model. Mice were assessed for weight change, liver biochemical profile, histology and hepatic phagocytes composition. Results: Flow cytometry analysis of hepatic nonparenchymal cells revealed reduced numbers of hepatic monocytes and Kupffer cells and an increase in hepatic MHC class II positive myeloid cells in immune cells restricted C/EBPβ deficient mice. Immune‐restricted C/EBPβ deficiency resulted in decreased weight gain and appearance of mild spontaneous liver inflammation. Nevertheless, In the CDA‐HFD steatohepatitis model, immune restricted C/EBPβ deficient and proficient mice exhibit similar grade of hepatic steatosis, liver enzymes levels and fibrosis stage. Conclusions: Immune‐restricted C/EBPβ deficiency leads to significant alteration in hepatic mononuclear phagocytes composition associated with spontaneous mild hepatitis. Steatohepatitis associated fibrosis is not dependent on C/EBPβ expression by immune cells. Abstract : Investigating the liver of immune restricted C/EBPβ‐deficient mice revealed major alteration in the composition of the intra‐hepatic myeloid cells pool associated with mild spontaneous hepatitis. Yet, immune cell restricted C/EBPβ‐deficiency did not confer protection from hepatic steatosis, inflammation and fibrosis, that are suggested to be influenced by C/EBPβ expression in nonimmune cells.